THE USE OF COMPLEMENTARY THERAPIES IN CHILDREN AND ADOLESCENTS WITH CANCER : A LITERATURE REVIEW - Setyawati, Anita; Mirwanti, Ristina; Nuraeni, Aan (Jurnal Perawat Indonesia, 2021)
Children and adolescents with cancer can experience unpleasant experiences, such as pain, anxiety, fatigue, sleep disturbances, balance disorders, and even mental, behavioral, and emotional disturbances. These negative experiences lead to decrease in quality of life. A recent research indicates that complement therapies can reduce the terrible effects of cancer. So this literature study aimed to identify the use of complementary therapies in children and adolescents with cancer. This study was a literature review that begins with a search for articles on digital databases, Science Direct and Google Scholar, using the keyword "complementary therapy AND cancer AND adolescents". The inclusion criteria in this study were articles published in 2010-2020, full text, research results, in English, and contained about the use of complementary therapies in children and adolescents (0-18 years) with cancer. Total of 12 articles were analyzed in this literature study. The results of this study showed there are four groups of complementary therapies for children and adolescents with cancer. Complementary and alternative medicine in general, cutaneous stimulation (massage therapy and acupressure), art therapy (group art therapy and creative art therapy), as well as body and mind therapy (eurythmy therapy and yoga), have both physiological and psychological effects. These four therapeutic groups can elicit physiological and psychological responses in children and adolescents with cancer. Patients can feel a reduction in the discomfort. Based on the results of this literature review, nurses and patients' families are expected to provide complementary therapies in the care of children and adolescents with cancer.